Biological screening of natural products and drug innovation in China - Wang, Ming-Wei (The Royal Society, 2007)
Natural products have been applied to human healthcare for thousands of years. Drug discovery in ancient times was largely by chance and based on clinical practices. As understanding of therapeutic benefits deepens and demands for natural products increase, previously serendipitous discoveries evolve into active searches for new medicines. Many drugs presently prescribed by physicians are either directly isolated from plants or are artificially modified versions of natural products. Scientists are looking for lead compounds with specific structures and pharmacological effects often from natural sources. Experiences and successes of Chinese scientists in this specialized area have resulted in a number of widely used drugs. The tremendous progress made in life sciences has not only revealed many pathological processes of diseases, but also led to the establishment of various molecular and cellular bioassays in conjunction with high-throughput technologies. This is advantageous and permits certain natural compounds that are difficult to isolate and purify, and compounds that are difficult to synthesize, to be assayed. The transition from traditional to empirical and to molecular screening will certainly increase the probability of discovering new leads and drug candidates from natural products.